Estudio de factibilidad para la Creación de una empresa de elaboración y comercialización de cosméticos a base de miel de abeja en el cantón Ventanas, año 2014. - Orozco Orozco, Wilton Wladimir (2015)
The topic study of feasibility is directed to the elaboration and commercialization of products Cosmetic facts with the help of bee honey, in the Ríos' Canton Windows County. The objective of they present it investigation it is to carry out a study of feasibility of Elaboration and Commercialization of Products Cosmetic facts with the help of bee honey, knowing that this type of products has gone constantly growing due to the great delight that people that consume them feel. A Study of Market was also elaborated, where you could evidence the offer and the demand that it exists in the so much county of products apícolas like of the teams of extraction apícola; in this chapter it was also described all the products to offer and the forms of promoting them in the market. He/she was carried out a Technical Study, to establish the correct location of the microempresa, the distribution of the areas and spaces that are required for the production, prosecution, packed and necessary packings that should be carried out according to the techniques and norms settled down by the market and the consumers. He/she took into account the advances of the information, modern norms of the productive, administrative, financial handling and the execution of the legal requirements that govern for the beginning and normal operation of the business, in topics as of production, handling of beehives, teams and tools, productivity and commercialization forms. The Economic Study and the financial viability where the analysis and financial evaluation of the project is determined that the initial investigation is of….